THE INFLUENCE OF LEARNING INTEREST AND MOTIVATION ON MATHEMATICS LEARNING ACHIEVEMENT IN CLASS VII STUDENTS OF SMP NEGERI 80 JAKARTA - Yohana Aplonia Pahanael; Santri Chintia Purba; Tan Hian Nio (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
This study aims to determine: (1) The relationship between interest and learning motivation on mathematics learning achievement among seventh-grade students at SMP Negeri 80 Jakarta; (2) The relationship between learning interest and mathematics learning achievement at SMP Negeri 80 Jakarta; (3) The relationship between learning motivation and mathematics learning achievement among seventh-grade students at SMP Negeri 80 Jakarta. The research method employed is a quantitative approach with a type of quantitative descriptive research. The research population includes all seventh-grade students at SMP Negeri 80 Jakarta. Meanwhile, the research sample consists of 75 students. The data collection technique in this research involves the use of instruments, namely: (1) learning interest questionnaire, (2) learning motivation questionnaire, and (3) even semester final exam scores. The obtained data were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques. The results of descriptive statistical analysis indicate that students' learning interest scores reached 77.3%, falling into the moderate category. Meanwhile, learning motivation reaches 73.3%, categorized as high, and learning achievement at 89.3% is in the category of beginning to develop.